2014
DOI: 10.7314/apjcp.2014.15.2.825
|View full text |Cite
|
Sign up to set email alerts
|

PDCD4 as a Predictor of Sensitivity to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer Patients

Abstract: Objective: The purpose of this study was to examine the role of programmed cell death 4 (PDCD4) expression in predicting tumor response to neoadjuvant chemoradiotherapy and outcomes for patients with locally advanced rectal cancer. Methods: Clinicopathological factors and expression of PDCD4 were evaluated in 92 patients with LARC treated with nCRT. After the completion of therapy, 4 cases achieved clinical complete response (cCR), and thus the remaining 88 patients underwent a standardized total mesorectal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…In most of the studies included in prognostic assessment, all clinical stages were represented in the respective cancer cases. However, the study reported by Dou et al [32], only focused on advanced stage rectal cancer, and the low PDCD4 expression within these patients was not significantly associated with the 5-year OS or DFS indicated by the 95% CI overlapping 1. Furthermore, the subcellular localization of the PDCD4 protein affects cancer behavior.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In most of the studies included in prognostic assessment, all clinical stages were represented in the respective cancer cases. However, the study reported by Dou et al [32], only focused on advanced stage rectal cancer, and the low PDCD4 expression within these patients was not significantly associated with the 5-year OS or DFS indicated by the 95% CI overlapping 1. Furthermore, the subcellular localization of the PDCD4 protein affects cancer behavior.…”
Section: Discussionmentioning
confidence: 93%
“…Combined analysis of the 20 studies in 10 papers that addressed OS [7, 15, 17, 18, 24, 2832] showed that reduced PDCD4 expression had an unfavorable impact on the OS of patients with solid tumors (HR: 2.24, 95% CI 1.93–2.60) (Table 3). Significant associations were observed in the univariate model (HR: 2.05, 95% CI 1.69–2.49) and multivariate model (HR: 2.52, 95% CI 2.01–3.16) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Programmed cell death Apoptotic index, 12,29 Bax, 14,16,30 BIRC5, [10][11][12][13] caspase-8, 31 hPEBP4, 32,33 M30, 34 MIB1, 15 p53, [14][15][16][17][18][19] PDCD4, 35 phospho-Akt, 21 XIAP, 36 YKL-40 27…”
Section: Cell Deathunclassified